2013
DOI: 10.1162/pres_a_00162
|View full text |Cite
|
Sign up to set email alerts
|

Telehaptic Perception of Delayed Stiffness Using Adaptive Impedance Control: Experimental Psychophysical Analysis

Abstract: Telehaptics is the science of transmitting touch-related sensations over computer networks. With respect to robot teleoperation, telehaptics emphasizes more on reliably reproducing physical properties of a remote environment, as mediated over a network through the use of appropriate haptic interfacing technologies. One of the main factors that can cause degradation of the quality of a telehaptic system is the presence of time delays. Inspired by concepts such as impedance-reflection and model-mediated telemani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Previous research reports a user study showing that MMT improves success rate of the task controlling forces exerted to objects in the presence of time delay [14]. Tzafestas and Velanas also show that the operator can discriminate smaller stiffness differences using MMT than directly rendering the environment force to the master [15].…”
Section: Introductionmentioning
confidence: 98%
“…Previous research reports a user study showing that MMT improves success rate of the task controlling forces exerted to objects in the presence of time delay [14]. Tzafestas and Velanas also show that the operator can discriminate smaller stiffness differences using MMT than directly rendering the environment force to the master [15].…”
Section: Introductionmentioning
confidence: 98%
“…Therefore developers try to minimize the delays within the system. Moreover, Tzafestas and Velanas [ 9 ] showed that delays deteriorate stiffness perception in a psychophysical experiment and presented an adaptive impedance control that was effective at improving this percept despite the presence of delays. Because there will always be delays between input and output in such systems, it is important to know the perceptual effects of such delays.…”
Section: Introductionmentioning
confidence: 99%